2013
DOI: 10.1021/ma400185j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Strong and Multifunctional Polyimide Nanocomposites Using Amimophenyl Functionalized Graphene Nanosheets

Abstract: We report an effective way to fabricate mechanically strong and multifunctional polyimide (PI) nanocomposites using aminophenyl functionalized graphene nanosheet (APGNS). APGNS was successfully obtained through a diazonium salt reaction. PI composites with different loading of APGNS were prepared by in situ polymerization. Both the mechanical and electrical properties of the APGNS/ PI composites were significantly improved compared with those of pure PI due to the homogeneous dispersion of APGNS and the strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 41 publications
1
64
2
1
Order By: Relevance
“…This result demonstrates the formation of covalent bonds between amino-phenyl groups and GO. N1s also showed three peaks at 397.7, 399.2, and 405.2 eV, corresponding to C-N, -NH 2 , and Ar-NH 2 , respectively [18]. The peak intensity of the -NH 2 groups of APGO (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…This result demonstrates the formation of covalent bonds between amino-phenyl groups and GO. N1s also showed three peaks at 397.7, 399.2, and 405.2 eV, corresponding to C-N, -NH 2 , and Ar-NH 2 , respectively [18]. The peak intensity of the -NH 2 groups of APGO (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Graphene-based PI composites exhibit the improved mechanical properties through the covalent bonding between the graphene nanofillers and PI matrix, as reported in previous studies [6,20,38]. However, the reinforced mechanism and the interaction behavior between the graphene filler and PI matrix need to be further investigated.…”
Section: In-situ Raman Spectroscopy Of Aptms-rgo/pi Compositesmentioning
confidence: 65%
“…Huang et al prepared the NH 2 -rGO/PI composite, and 2 wt% NH 2 -rGO afforded a 40% and 42% increment for the tensile strength and the modulus, respectively [6]. Park et al reported the increased mechanical property of FG/PI composites when 3 wt% FG was covalently bonded with PI matrix [20,21], and further prepared the iodo functionalized GO/PI nanocomposites, showing a significant improvement for electrical conductivity and mechanical properties [22]. Recently, Liao et al presented a 240% increase in the tensile strength at 0.3 wt% NH 2 -functionalized GO [23].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum value of tensile strength is 133 MPa At 5 wt% MWNTs loading is 40% higher than that of the pure polyimide. When the mass percentage of MWNTs is 9 wt%, the value is 108 MPa, also higher than the pure PI [10].…”
Section: IIImentioning
confidence: 89%